ANALISIS TINGKAT KEUNTUNGAN PADA USAHATANI JAHE MERAH (Zingiber officinale Roscoe) DI DESA DANAU RATA KECAMATAN KISAM TINGGI KEBUPATEN OKU SELATAN - aisyah aisyah (JASEP, 2022)
Ginger is a spice or medicinal plant commodity that has great potential for intensive commercial-oriented (agribusiness) cultivation. Ginger has benefits as a traditional medicine, a basic ingredient for the food and beverage industry, ginger oil, cooking spices and others. Apart from being consumed domestically, ginger is also exported as a non-oil and gas commodity. Ginger is one of Indonesia's spice export commodities which plays a major role in earning the country's foreign exchange. Ginger is exported in the form of fresh ginger, dried ginger, essential oil and oleoserin. The rapid growth of the traditional medicine industry and other industries that use ginger as a raw material causes the demand for ginger to increase from year to year. This trend is a good start to start developing ginger agribusiness. OKU Selatan Regency is one of the highest ginger producing centers in South Sumatra Province with a production of 398.9 tons with a provincial share of 29.58% in 2019. The production produced from year to year has increased, this is because many farmers are have started cultivating red ginger. The reason farmers switch to red ginger is because the maintenance of red ginger is quite easy and the sale value is relatively high. This study aims to calculate the income and profit levels of red ginger farming in Danau Rata Village, Kisam Tinggi District, OKU Selatan District. The research method used in this study is a survey method while the sampling method is purposive sampling. The results showed that the average production cost incurred was Rp. 40,294,745/ha per production process, average income of Rp. 119,805,000/ha per production process. The R/C ratio and B/C ratio were 2.98 and 1.98 respectively, this indicated that red ginger farming was profitable and feasible to develop. And the production BEP value is 7,902 kg/ha and the BEP price is Rp. 5.046/kg.Keywords: Ginger, Farming, and Profitability